Physiological and gene expression analysis of Hevea brasiliensis under drought stress - Mostafa Mohammadi Nodehi; Mohtaram Mahmoudieh; Alireza Taleei; Valiollah Mohammadi; Mohammad Mahbubur Rahman; Meisam Zargar; Mohammad Reza Naghavi (PLoS ONE, 2025)
Natural rubber, derived mainly from the Hevea brasiliensis tree, is a highly valuable biopolymer. This study examined the effects of drought stress on rubber seedlings, focusing on their physiological responses and gene expression under three irrigation conditions: well-watered (control), mild drought, and severe drought. Results indicated that as drought severity increased, the relative water content in the leaves decreased. The level of proline was significantly higher under severe drought but decreased during mild drought stress. Malondialdehyde levels increased in leaves under drought stress, while antioxidant enzymes varied: ascorbate peroxidase and catalase activity increased under mild drought stress. The guaiacol peroxidase (GPX) activity rose under drought condition, indicating adaptive oxidative and osmotic responses. Gene expression analysis demonstrated significant down-regulation of the rubber biosynthesis gene 3-hydroxy-3-methylglutaryl-CoA reductase ( HMGR ) under drought conditions, indicating a reduction in rubber production. In contrast, the expression of cis-prenyltransferase was up-regulated, suggesting a compensatory mechanism to maintain rubber synthesis despite a shortage of precursors. HMG-CoA synthase significantly decreased under severe drought stress, whereas transferase activator exhibited non-significant changes during drought conditions. Additionally, an inverse relationship was identified between HMGR expression and GPX activity, suggesting that increased levels of reactive oxygen species during drought stress may inhibit antioxidant responses, ultimately leading to the down-regulation of HMGR . Drought stress suppresses HMGR expression, reducing rubber yield. Preventing the downregulation of this gene under drought conditions could be a key focus for future research. These findings enhance our understanding of the molecular mechanisms of drought adaptation in rubber seedlings and provide insights for breeding resilient genotypes.